INDUSTRY 4.0 AWARENESS AND MATURITY LEVEL OF TURKISH INDUSTRY (Third Sector Social Economic Review, 2023)
With the reflections of the radical changes in the scientific and technological field on production, there have been four major industrial revolutions until today, the effects of which have gradually deepened. In the first industrial revolution, the production of machines with steam power was followed by mechanization with electrical energy in the second industrial revolution, and automation with the advances in semiconductor technologies in the third industrial revolution. With Industry 4.0, which was introduced in Germany in 2011, the world began to witness a new industrial revolution with the combination of many destructive technology components. Developed countries have entered this new race in order to get a share of the economic benefits and competitive advantages they will provide. It is clear that the leader countries of this race will carry the production made in countries with cheap production cost indices to their own countries. For Türkiye, it is extremely vital to realize the Industry 4.0 transformation in order not to lose the production advantage captured by cheap production factors. With this study, a model was created from the most basic elements of Industry 4.0 transformation and it was aimed to determine the Industry 4.0 awareness and maturity level of Turkey's 1000 leading industrial enterprises with the survey study based on this model. Feedback was received from 459 enterprises and analyzes were made using SPSS and AMOS programs. As a result of the analyzes made, the Industry 4.0 awareness level of the Turkish industry was determined as 3.74/5 (experienced/close to expert level) and the maturity level as 3.16/5 (experienced level), according to the model created.
Keywords: Industry 4.0; Industrial Revolution; Digitalization; Digital Transformation; Digital Maturity